Anemia and Outcome in Outpatients With Peripheral Artery Disease. (May 2016) - Perez, Paulina; Esteban, Carlos; Caballero, Pedro Enrique Jiménez; Muñoz-Torrero, Juan Francisco Sánchez; Soria, María Teresa Pascual; Aguilar, Eduardo; Rodríguez, Lorenzo Ramón Álvarez; Sahuquillo, Joan Carles; Díaz, Ana María García; Monreal, Manuel; ,
The influence of anemia on outcome in stable outpatients with peripheral artery disease (PAD) has not been consistently investigated. We used data from the Factores de Riesgo y ENfermedad Arterial (FRENA) Registry to compare ischemic events and mortality rates in stable outpatients with symptomatic PAD and anemia. Of 1663 patients with PAD, 208 (12.5%) had anemia. Over 18 months, patients with anemia had a higher rate of myocardial infarction (MI; rate ratio [RR]: 2.10; 95% confidence interval [CI]: 1.04-3.99), limb amputation (RR: 2.98; 95%CI: 1.70-5.05), and higher mortality (RR: 3.58; 95%CI: 2.39-5.28) than those without anemia. The rates of ischemic stroke (RR: 0.75; 95%CI: 0.23-1.93) and major bleeding (RR: 0.93; 95%CI: 0.15-3.51) were similar. On multivariable analysis, anemia was associated with an increased risk to die (hazard ratio [HR]: 2.32; 95%CI: 1.53-3.50) but not to develop MI (HR: 1.49; 95%CI: 0.73-3.05) or to have limb amputation (HR: 1.49; 95%CI: 0.86-2.59). In stable outpatients with PAD, anemia was associated with increased mortality but not with an increased rate of subsequent ischemic events or major bleeding.